Health related quality of life in older or frail patients with advanced colorectal cancer treated with dose reduced capecitabine. Issue 6 (November 2018) - Breadner, Daniel; Vincent, Mark David; Jonker, Derek; Cripps, Christine; Klimo, Paul; Biagi, James; Lam, Wendy; O'Connell, Anne; Whiston, Frances; Stitt, Larry; Welch, Stephen
Abstract: Objectives: Palliative chemotherapy's role is to prolong survival while minimizing treatment toxicities to preserve or improve quality of life. We have recently published a phase II trial of dose reduced capecitabine in older or frail patients with advanced colorectal cancer (aCRC). We herein provide a robust analysis of the health related quality of life (HRQoL) data from our trial. Methods: A single arm multi-centered phase II trial of dose reduced capecitabine (1500 or 2000 mg/m 2  days one-fourteen q21 days) in older or frail patients. Participants (182 patients) were asked to complete Functional Assessment of Cancer Therapy general questionnaire (FACT-G) at enrollment, after each cycle of capecitabine, and once upon completion, if possible. Results: 157 patients completed a baseline questionnaire (86%), and 137 patients (75%) completed at least one subsequent questionnaire. The mean baseline score was 81.6, out of a possible 108. The mean score peaked at 92 after cycle 10. The mean change from baseline was always positive. Patients achieving the minimal clinically important difference (MCID) ranged from 30% to 45% during treatment. Higher baseline FACT-G and Physical Well-being score were independently prognostic for improved survival (p = 0.006 and p < 0.0001, respectively). Time until definitive deterioration (TUDD) was insignificantly longer in patients with a higher baseline FACT-G (p = 0.18). Conclusion: Baseline HRQoL scores were independently prognostic for survival, supporting their importance. Compared to full dose, reduced dose capecitabine has previously demonstrated equivalent efficacy and reduced toxicity. We have reported dose reduced capecitabine improves quality of life in older or frail patients with aCRC, further supporting its use in the management of aCRC.